MAKARA OF ADAN-ADAN TEMPLE: THE ART STYLE DURING THE KAÁ¸IRI PERIOD: MAKARA CANDI ADAN-ADAN: GAYA SENI MASA KAÁ¸IRI - Sukawati Susetyo (Berkala Arkeologi, 2020)
Abstract This paper discusses the makara found at Adan-Adan Temple, Kediri. So far, it is the largest makara in Indonesia and, in terms of iconography, has distinctive features. The data was collected through detailed observations both directly in the field or through photographs. This study employed a comparative analysis, i.e. comparing the collected data to the makaras from different periods (the Ancient MatarÄm, the SrÄ«wijaya, and the SiÅ‹hasÄri). From these comparisons, it is known that the makara at Adan-Adan Temple has special characteristics, i.e. different depictions between the makara on the left and the right as can be seen from the figure of a mythical creature inside the makaraâ€™s mouth, from the sculpture on the front of the makara, and on the back of the makara. This particularity may be included as an art style of the Kaá¸iri period (the transitional period of from Ancient MatarÄm to SiÅ‹hasÄri). Abstrak Tulisan ini memaparkan tentang makara yang ditemukan pada waktu penelitian di Candi Adan-Adan, Kediri. Makara Candi Adan-Adan sejauh ini merupakan makara terbesar di Indonesia dan dari segi ikonografi mempunyai ciri yang khas. Pengumpulan data dilakukan ketika penelitian melalui pengamatan detil baik secara langsung atau melalui foto, kemudian mendeskripsikannya. Analisis dilakukan dengan studi komparasi yaitu membandingkan makara Candi Adan-Adan terhadap makara-makara dari masa yang berbeda, yaitu masa MatarÄm Kuno, masa ÅšrÄ«wijaya, dan masa SiÅ‹hasÄri. Melalui perbandingan tersebut diketahui bahwa makara Candi Adan-Adan mempunyai ciri-ciri khusus berupa pembedaan penggambaran yang dapat diamati antara makara di sebelah kiri dan kanan, pada figur makhluk mitos yang berada dalam mulut makara; pada pahatan di bagian depan makara; dan pada bentuk bagian belakang makara. Kekhasan ini kiranya dapat dimasukkan sebagai gaya seni masa Kaá¸iri (masa peralihan dari MatarÄm Kuno ke SiÅ‹hasÄri).